Salt-inducible kinase inhibition suppresses acute myeloid leukemia progression in vivo - Tarumoto, Yusuke (Blood, 2020)
Lineage-defining transcription factors (TFs) are compelling targets for leukemia therapy, yet they are among the most challenging proteins to modulate directly with small molecules. We previously used CRISPR screening to identify a salt-inducible kinase 3 (SIK3) requirement for the growth of acute myeloid leukemia (AML) cell lines that overexpress the lineage TF myocyte enhancer factor (MEF2C). In this context, SIK3 maintains MEF2C function by directly phosphorylating histone deacetylase 4 (HDAC4), a repressive cofactor of MEF2C. In this study, we evaluated whether inhibition of SIK3 with the tool compound YKL-05-099 can suppress MEF2C function and attenuate disease progression in animal models of AML. Genetic targeting of SIK3 or MEF2C selectively suppressed the growth of transformed hematopoietic cells under in vitro and in vivo conditions. Similar phenotypes were obtained when cells were exposed to YKL-05-099, which caused cell-cycle arrest and apoptosis in MEF2C-expressing AML cell lines. An epigenomic analysis revealed that YKL-05-099 rapidly suppressed MEF2C function by altering the phosphorylation state and nuclear localization of HDAC4. Using a gatekeeper allele of SIK3, we found that the antiproliferative effects of YKL-05-099 occurred through on-target inhibition of SIK3 kinase activity. Based on these findings, we treated 2 different mouse models of MLL-AF9 AML with YKL-05-099, which attenuated disease progression in vivo and extended animal survival at well-tolerated doses. These findings validate SIK3 as a therapeutic target in MEF2C-addicted AML and provide a rationale for developing druglike inhibitors of SIK3 for definitive preclinical investigation and for studies in human patients.